The Impacts of Gold Mining on Vegetation and Mycorrhizal Colonization in Northern Canada - Mediouni, Sarah (Scholars Commons @ Laurier, 2019)
Gold mining is an important part of economic development in Northern Canada. A large portion of the gold that is found in the North is contained within arsenopyrite ores, therefore, arsenic contamination is of special concern. Little is known regarding the impacts of arsenic on plants and mycorrhizae in Northern Ecosystems. Arsenic has been shown to negatively impact plant growth and seed germination in some temperate species, while others are tolerant and can accumulate arsenic concentrations over 1000 mg/kg. In temperate regions, arbuscular mycorrhiza can accelerate the remediation process in gold mines by supporting plant growth in poor soil conditions but they have also been shown to be negatively impacted by arsenic exposure. To assess impact of arsenic on plants and mycorrhizae, field studies were undertaken at Tundra Mine, an inactive gold mine 250 km northeast of Yellowknife. Vegetation surveys were conducted and plant samples were collected for arsenic accumulation and mycorrhizal colonization at 4 sites near a tailings containment area and 4 reference sites further away from the mine. Arsenic concentrations in plants ranged from 0.08 ± 0.01 mg/kg to 870 ± 230 mg/kg. The highest arsenic concentrations were consistently found in plants that grew in the 4 sites adjacent to the tailings containment area. Carex aquatilis contained the highest concentration of arsenic at those sites making it a good potential candidate for phytoremediation (roots = 870 ± 230 mg/kg; shoots = 141 ± 49.0 mg/kg). At the sites with the two highest soil arsenic concentrations all plants sampled exceeded arsenic concentrations recommended for plant material designated for human consumption (3.5 mg/kg in fish) and animal feed (8 mg/kg) in some cases by up to three orders of magnitude. Non-metric multidimensional scaling results using vegetation survey data showed that plant communities at the 4 sites adjacent to the mine were distinct from the 4 reference sites. Both arbuscular mycorrhizal and dark septate endophyte colonization was ...